CAPACITY CARDIORRESPIRATÓRIA IN CHILDREN AND YOUNG: A STUDY OF VALIDATION IN TEST OF ASCENTS AND DESCENDINGS OF BANK ELETRONICO PROTOCOL OF CIRILO (SOUSA, 2001) IN THE JOÃO CITY PERSON. (Fiep Bulletin - online, 2014)
VO2máx as predicted of the physical fitness state is recognized and enough used, expressing the amount of captured oxygen and used in a physical effort, indicating state of conditioning cardio-respiratory. To present research he/she concentrates on the analysis of VO2máx predicted in test of bank electronic Protocol of Cirilo (SOUSA, 2001) in children of the public net of the city of João Pessoa. The sample was composed by 268 children, being 128 female (FEM) and 140 male (MAS) with age group from 07 to 12anos of age.  A portable stature meter was used, it balances digital, I support electronic (SOUSA, 2001); POLAR frequency meter, Scale of Accommodation Postural and the table of Borg. The research gave beginning after the authorization for the Committee of Ethics in Research, and the collection was accomplished after signature of the consent term by the parents, being applied the bank test mentioned previously. It was verified that the children MAS they obtained the largest average of VO2máx 35,46 + 1,97ml.kg/min-1 standing out in all of the ages when compared the children FEM, that obtained an average of 33,50 + 3,24 ml.kg/min-1. The analyzed variable differed his behavior when being compared between goods and ages, result this could be justifiable for the selection of activities that you/they involve the daily of the groups (MAS and FEM) and the physical demands of these.
Keywords: VO2 maximum; bank test; children; capacity cardio-respiratory